Paradox of Criminal Responsibility for Persons with Mental Disabilities in the 2023 Penal Code - Nasrullah; Munawir, Zaini (Jurnal Ilmu Kepolisian, 2025)
Criminal law reform in Indonesia through the ratification of the new Criminal Code has given rise to various complexities in legal governance, including the treatment of individuals with mental disabilities involved in criminal cases. Although the new Criminal Code is designed to integrate the principles of respect for Human Rights (HR) and emphasize a more humanistic approach in the law enforcement process, several provisions within it reveal normative contradictions. In particular, criminal regulations for people with mental disabilities often contradict the standards set out in the Convention on the Rights of Persons with Disabilities (CRPD). This phenomenon has sparked legal and ethical debates regarding the adequacy of the domestic regulatory framework regarding international commitments. Furthermore, law enforcement practices by the police, who are at the forefront of handling such cases, tend to prioritize a repressive approach rather than a rehabilitative one, thus potentially leading to human rights violations. This study examines the inconsistency between the normative ideals of the new Criminal Code and the factual implementation in the field, while emphasizing the urgency of developing policies that are inclusive, based on restorative justice, and consistently respect the dignity of individuals with mental disabilities. This research employed a qualitative method based on a normative legal approach, utilizing a statutory and conceptual approach as the primary analytical frameworks. The data in this study are sourced from a comprehensive literature review that encompasses laws and regulations, legal documents, previous research results, and various relevant scientific works. The data processing process is carried out through in-depth legal analysis to identify, interpret, and evaluate applicable legal norms. This approach allows research to produce a comprehensive understanding of the legal issues studied, while providing significant academic contributions to the development of legal theory and practice.